Effects of Ambient Environmental Factors on the Stereotypic Behaviors of Giant Pandas (Ailuropoda melanoleuca) - Liu, He (PLoS One, 2017)
Stereotypies are commonly observed in zoo animals, and it is necessary to better understand whether ambient environmental factors contribute to stereotypy and how to affect animal welfare in zoo settings. This study investigated the relationships between stereotypic behaviors and environmental factors including ambient temperatures, humidity, light intensity, sound intensity and number of visitors. Seven giant pandas were observed in three indoor enclosures and three outdoor enclosures. Environmental factors were measured for both indoor and outdoor enclosures and the effect they had on stereotypical behaviors was investigated. Our research found that light intensity significantly correlated with all stereotypies behaviors. Higher environmental temperature reduced the duration of pacing but increased the frequency of pacing, the duration and frequency of door-directed, meanwhile the duration of head-toss. However, we found no noticeable effect of humidity on stereotypic behaviors except for the frequency of head-toss. We also found that sound intensity was not correlated with stereotypies. Finally, the growth of visitors was negatively associated with the duration of door-directed. These results demonstrated that various environmental factors can have significant effects on stereotypic behaviors causing the expression of various stereotypies. Thus, stereotypies in zoo animals may not simply represent suboptimal welfare, but rather might be adopted as a means of coping with an aversive environment.